The Effects Of Tax Avoidance, Managerial Ownership, And Dividend Policy On Firm Value - Anggara, Winny Kezia; Subandi, Hendi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to assess and analyze the impacts of tax avoidance, managerial ownership, and dividend policy on firm value. The data was harvested from a sample of 38 food-and-beverage companies listed on the Indonesia Stock Exchange during the 2021-2023 period and was analyzed through multiple linear regression. This study finds that tax avoidance negatively affects the firm value and that managerial ownership and dividend policy positively impact the firm value. The findings support the Agency and Signal Theory, recommending that companies reduce tax avoidance, enhance managerial ownership, and improve dividend policy to increase firm value.